We burn daylight a novel - Johnston, Bret Anthony 1971- (Random House, 2024)
"Waco, Texas, 1993. A charismatic figure known as the Lamb gathers his flock and his weapons to await the fulfillment of God's prophesy for the last days. "In olden days, when somebody said you've gone to Texas, that meant you'd lost your marbles," the Lamb told his followers. "But we're heading to Texas because we ain't crazy." From all over the world they come to join the Lamb, lost on earth and desperate to be found in heaven. The novel follows a teenage girl named Jaye and her mother as they leave their California home to move in to the Lamb's compound and be counted at the time of redeeming. Jaye is a smartass kid who doesn't care for rules much less religion, and couldn't understand what her mother saw in the Lamb-whom she calls by his birth name, "Perry"-a landscaper who wanted to be a guitar god and somehow became an actual god instead. But Jaye is looking for something, and when she meets Roy, the sheriff's son, the two teenagers are drawn to each other, even as they careen toward the fulfillment of the Lamb's final, violent visions in this prairie epic of the Montagues and the Capulets"--